2018
DOI: 10.1371/journal.pmed.1002668
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient air pollution and daily hospital admissions for ischemic stroke: A nationwide time-series analysis

Abstract: BackgroundEvidence of the short-term effects of ambient air pollution on the risk of ischemic stroke in low- and middle-income countries is limited and inconsistent. We aimed to examine the associations between air pollution and daily hospital admissions for ischemic stroke in China.Methods and findingsWe identified hospital admissions for ischemic stroke in 2014–2016 from the national database covering up to 0.28 billion people who received Urban Employee Basic Medical Insurance (UEBMI) in China. We examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
135
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(151 citation statements)
references
References 52 publications
13
135
3
Order By: Relevance
“…For example, the most informative pollutant of traffic emissions NO 2 . The association were comparable to previously studies [6,11,12,16].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For example, the most informative pollutant of traffic emissions NO 2 . The association were comparable to previously studies [6,11,12,16].…”
Section: Discussionsupporting
confidence: 91%
“…The identification of potentially vulnerable subpopulation has significant implications for public health [12], therefore we stratified the stroke cases into < 65 and ≥ 65 years groups. For ischemic stroke, we found that the effect estimates of SO 2 were higher for the < 65 than that in the ≥65 age group, which is the opposite of Tian et al [12]. This may be due to the varied activity patterns for different age groups in different cities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the respiratory system, it can likewise cause neurological disorders. SO 2 was uncovered being associated with stroke in which the risk of hospital admissions for ischemic stroke would raise 1.37% (1.05%-1.70%) with per 10 g/m 3 increase of SO 2 concentrations [64]. A recent study did not find significant effects on vascular dementia (OR = 0.95 for per 1 ppm SO 2 concentration increased) [42].…”
Section: Mechanisms Of the Association Between So 2 And Admentioning
confidence: 97%
“…In China, several previous studies have shown that ambient CO has a statistically significant adverse effect on human health, could increase cause-specific mortality [2,3] and morbidity [4,5]. However, assessing the CO-related effect on human health with the mortality data, implicitly ignore the unequal weights to the deaths of young people and elderly.…”
mentioning
confidence: 99%